Analisis Persepsi Pegawai Terhadap Penggunaan E-billing dalam Proses Pembayaran Pajak di Kementerian Ketenagakerjaan RI Jakarta Selatan: ANALYSIS OF EMPLOYEE PERCEPTION TOWARDS THE USE OF E-BILLING IN THE TAX PAYMENT PROCESS AT THE MINISTRY OF MANPOWER OF THE REPUBLIC OF INDONESIA, SOUTH JAKARTA - Retha Anastasia Putri Simorangkir; gurhanawan (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
Analysis of Employee Perceptions on the Use of E-Billing in the Tax Payment Process at theMinistry of Manpower of the Republic of Indonesia, South JakartaThis research is motivated by the ongoing challenges in the implementation of the e-Billing systemwithin the Ministry of Manpower of the Republic of Indonesia in South Jakarta, despite its design toimprove efficiency and transparency in tax administration. Some employees still face difficulties inunderstanding procedures, have limited digital literacy, and hold negative perceptions toward thesystem. This study aims to analyze employees’ perceptions of the use of e-Billing in the tax paymentprocess, identify the influencing factors, and formulate solutions to improve the system’s effectiveness.This research uses a descriptive qualitative approach, with data collected through observation,interviews, and documentation. The data analysis technique applies Miles and Huberman’s interactivemodel, which includes data reduction, data display, and conclusion drawing. The findings indicate thatemployees’ perceptions are influenced by perceived ease of use, perceived usefulness, andorganizational support. These findings are analyzed using the Technology Acceptance Model (TAM)framework. The study concludes that increasing employee understanding through training andtechnical assistance is essential to ensure the optimal implementation of the e-Billing system ingovernment institutions.